Human resource development: Proactive preparation to manage crises - Hosie, Peter (2006)
Significant increases in the incidence of global terrorism, serious criminal activities, and the ever-present threat of natural catastrophes have emphasised the need for businesses to prepare for managing crises. A more systematic and robust conceptual approach has long been overdue to identify how businesses can effectively prepare to deal with crises. A shared understanding between business stakeholders is needed of what is meant by crisis management in a commercial context. This required a consolidation of the state of the literature, particularly a definition and description of what constitutes crises. Proactive crisis management policies and practices can contribute to businesses capacity to manage crises as well as to provide a safe working environment for employees. The preparation stage of crisis management was identified as the beginning of a strategic response to recover from crises. Human resource development is promoted as a key component of the preparation to respond to and subsequently management of crises.